POLA PERKEMBANGAN RUANG DI KABUPATEN SEMARANG DENGAN MEMANFAATKAN DATA CITRA LANDSAT - Pangi Pangi; Muharar Ramadhan; Khristiana Dwi Astuti; Intan Muning Harjanti; Reny Yesiana (Jurnal Pengembangan Kota, 2017)
The development of the city is influenced by the growth on the physical, economic, and social activities in the city. In the case of Semarang Regency, this development is included in the category fairly fast, particularly after the opening of toll road Semarang-Bawen. By utilizing remote sensing technology and satellite imagery, the pattern of these developments can be mapped and analyzed. The purpose of this study was to identify the pattern of development of space in Semarang Regency by using multitemporal Landsat images. The application of these images can be a mean of monitoring and controlling mechanism of the urban growth in the fast growing city in Central Java, such as in Semarang Regency. Hence, the focus of this analysis is on data of built up area. During the period of 43 years (1972 - 2015) land use change that occurred in the district of Semarang had increased for about 13,000 Ha or an average of 300 ha/year. The biggest changes are located in the Tengaran, Susukan and Bergas sub district that grow more than 20 ha / year.